Resonance ionization of titanium: high useful yield and new autoionizing states. Issue 11 (19th September 2018) - Trappitsch, Reto; Savina, Michael R.; Isselhardt, Brett H.
Abstract : To facilitate analyses of trace amounts of titanium in atom-limited samples, we established a new three-step resonance ionization scheme. Using time-of-flight mass spectrometry we show that the new scheme can be easily saturated, yields stable isotope measurements, and can achieve an overall useful yield of 18%. Abstract : The isotopic composition of titanium in meteoritic phases can be used to decipher processes such as stellar nucleosynthesis and galactic chemical evolution. In order to facilitate analyses of trace amounts of titanium in atom-limited samples, we established a new three-step resonance ionization scheme. The scheme was developed using titanium–sapphire lasers and we show that it can be easily saturated and that it yields stable isotope measurements. Using the LION (Laser Ionization Of Neutrals) instrument we demonstrate a useful yield of 10.1% ± 1.6% when ionizing from the ground state. We determined the population of two low-lying electronic states within the ground state multiplet and show that accessing all three levels of the ground state manifold would result in an overall useful yield of ∼18%. The useful yield agrees well with expectations based on prior analyses of uranium using LION. In addition, we report the energy levels of nine new autoionizing states between 56 217 cm −1 and 57 086 cm −1 .